STRESS PROTEINS: NOMENCLATURE, DIVISION AND FUNCTIONS - Kopecek, Petr; Altmannova, Karla; Weigl, Evzen (Biomedical papers, 2001)
The heat shock response, characterized by increased expression of heat shock proteins (Hsps) is induced byexposure of cells and tissues to extreme conditions that cause acute or chronic stress. Hsps function as molecularchaperones in regulating cellular homeostasis and promoting survival. If the stress is too severe, a signal that leadsto programmed cell death, apoptosis, is activated, thereby providing a finely tuned balance between survival anddeath. In addition to extracellular stimuli, several nonstressful conditions induce Hsps during normal cellulargrowth and development. The enhanced heat shock gene expression in response to various stimuli is regulated byheat shock transcription factors.
Keywords: Stress proteins / Hsp / Molecular chaperon